PASSIVE SURVEILLANCE OF GASTROINTESTINAL PARASITES IN BUFFLAOES OF MANDI BAHAUDDIN AND GUJRAT DISTRICTS OF THE PUNJAB - Khalil-ur-Rehman; K. Javed M.T. Tunio; Z. H. Kuthu (Journal of Animal and Plant Sciences, 2009)
The study was carried out to find out the occurrence of parasitic infestation in buffaloes in Mandi Baha-ud-din and Gujrat districts of the Punjab. A total of 28880 faecal samples were examined in diagnostic laboratories from 1994 to 2004 out of which 26408 (91.44 percent) were positive for different parasites during the study period. The prevalence of trematodes, nematodes, cestodes and mixed infestation in buffaloes was 49.01, 28.55, 7.08 and 15.19 percent, respectively. Maximum prevalence was observed from January to September, while minimum parasitism was observed from October to December. The results of the present study indicated that there was heavy worm load present in buffaloes causing huge economic loss to the farmers by reducing milk production and retarded growth. The worm load can be minimized through better housing and husbandry practices besides use of proper anthelmintics.
Keywords: Cestodes; Nematodes; Trematodes; Buffaloes; Pakistan